Evaluation of the whole proteome to design a novel mRNA-based vaccine against multidrug-resistant Serratia marcescens - Naveed, Muhammad; Mughal, Muhammad Saad; Jabeen, Khizra; Aziz, Tariq; Naz, Sumaira; Nazir, Nausheen; Shahzad, Muhammad; Alharbi, Metab; Alshammari, Abdulrahman; Sadhu, Satya Sai (Frontiers in Microbiology, 2022)
Serratia marcescens is a gram-negative bacterium and is one of the known disease-causing pathogens. It is resistant to ampicillin, macrolides, cephalosporins, cefotaxime and ceftazidime. Only Gentamicin proved to be effective against S. Marcescens. By causing epigenetic alterations, bacteria can also become resistant to any antibiotics. Many Proteins regarding epigenetics were studied and four proteins were selected in this regard to evaluate epitopes and further used in develop of mRNA vaccine. Cellular and humoral immunity was elicited by a variety of immune-informatics tools were used to build this mRNA vaccine. Molecular docking was performed between epitopes and MHC alleles. The vaccine was developed using 37 epitopes, an adjuvant which is TLR4 agonist called RpfE, subcellular trafficking structures, secretion boosters, and linkers. This proposed architecture was found to cover 99.6% of the population during testing. It was also proven to be both effective and safe throughout testing. To confirm our idea, we ran an in silico immunological simulation of the vaccination. Codon optimization was also done to ensure that mRNA reaches the cytoplasm of a human host and is translated efficiently. TLR-4 and TLR-3 were also docked against secondary and tertiary structures of the vaccination peptide. Furthermore, Stability of the vaccine was confirmed through Molecular dynamics simulation. In short, this vaccine construct can be potential candidate against Serratia marcescens and suitable for in vitro analyze to validate its effectiveness.